Analisis Green Marketing, Green Advertising, dan Brand Image dalam Membentuk Purchase Decision dan Customer Satisfaction dalam Studi Kasus Pengguna Skincare di DKI Jakarta - Michael Lambok; Usep Suhud; Meta Bara Berutu (Indo Publishing, 2026)
This study aims to analyze the effects of green marketing, green advertising, and brand image on purchase decision and customer satisfaction among The Body Shop skincare users in the DKI Jakarta area. A quantitative approach was employed using a survey method through online questionnaires. The population consisted of The Body Shop skincare users aged 21–55 years living in DKI Jakarta, with 400 respondents selected using purposive sampling. Data were analyzed through validity and reliability tests, as well as hypothesis testing using SEM. The results indicate that green marketing and brand image have a positive and significant effect on purchase decision, while green advertising has no direct effect. Furthermore, brand image and purchase decision positively and significantly influence customer satisfaction. In contrast, green marketing and green advertising do not have a direct effect on customer satisfaction.